Rancang Bangun Sistem Informasi Surat Perintah Perjalanan Dinas - Ester Laekha (Maranatha University Press, 2017)
Abstract — This paper will propose information system design for SPPD application. Currently Research Center for Physics LIPI still implement manual way to issue SPPD. By observing manual way of issued SPPD and reference study of normalization data method, a design of information system is proposed. It is found that third form of normalization is enough to organize data inside database. Keywords—Data Normalisation , Information System, SPPD.